Computer tomography of the brain in Hamilton. - Banna, M. (1975)
Computer tomography, a new noninvasive, rapid and easily tolerated technique of brain examination, has been evaluated by analysis of 1000 examinations. It is much more sensitive than conventional radiographic techniques and can resolve soft-tissue structures that differ only slightly in density. It also provides direct visualization of the ventricular system. The range of clinical applications is wide; it is especially useful in differentiating intracerebral hemorrhage from infarction, and in demonstrating many brain tumours, particularly supratentorial, though enhancement with a water-soluble contrast medium injected intravenously is often necessary.